CTA Annual Report 2008: highlights: CTA responds to the winds of changes: - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
From the large number of projects we ran during the year, it is hard to pick just a few, but for me the comprehensive study on telecentres (see page 11), and the seminar on Climate Change (see page 6) must stand as milestones. Download to read more...